A STUDY OF STUDENTS' SPEAKING DIFFICULTIES AT ENGLISH CLUB SMA NEGERI 7 SAMARINDA - Aida Qoir Setyaning; Phil Maria T Ping; Yuni Utami Asih (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2024)
This study aimed to investigate students’ speaking difficulties and the reasons behind the difficulties. This qualitative case study gathered data through speaking task assessment, questionnaire, and semi-structured interview which analyzed thematically from English Club in SMA Negeri 7 Samarinda in the academic year of 2024 who were selected based on the 3 lowest score of the questionnaire. Additionally, students’ speaking difficulties in speaking were categorized into shyness and inhibition, low participation of individuals, finding things to say, and L1 use, meanwhile the reasons behind students’ speaking difficulties were categorized as psychological factors, linguistic factors, and lack of practice factors based on some theories. The result showed that English Club students experienced some difficulties in speaking, such as overuse of L1, confused in finding things to say, shyness and inhibition, and low participation of individuals. This study also found out that the possible reasons behind the difficulties were from linguistic factors: lack of vocabularies, lack of pronunciation, and lack of grammar. Moreover, psychological factors which related to fear of making mistakes, self- confidence, and language anxiety also contributed to the difficulties with the lack opportunities to practice inside and outside the class. Hence, English Club students were still lack of linguistical features in speaking which also affect their psychological and became hesitate to speak in English Club meetings.